Synergistic use of ground-based multi-instrument platforms and satellite recordings to investigate the aerosol-cloud-dynamic interaction in Cyprus - Panahifar, Hossein; Poutli, Maria; Kotsias, George; Nisantzi, Argyro; Michaelides, Silas; Hadjimitsis, Diofantos G.; Seifert, Patric; Ansmann, Albert; Mamouri, Rodanthi-Elisavet (My University, 2025)
This study demonstrates the capability of the Cyprus Atmospheric Remote Sensing Observatory (CARO) to investigate aerosol cloud–dynamic interactions through synergistic measurements from ground-based and satellite platforms. Co-located lidar and radar systems, including the PollyXT multi-wavelength Raman-polarization lidar and the MIRA-35 Doppler cloud radar, were combined with satellite observations from the ATLID instrument aboard EarthCARE. A case study on 17–18 March 2025 revealed a lofted Saharan dust layer descending from approximately 6 km to 2 km altitude, followed by the formation of an ice-precipitating altocumulus cloud deck between 4 and 7 km. Radar reflectivity, Doppler velocity, and spectral width profiles confirmed hydrometeor sedimentation, vertical cloud layering, and virga signatures. CloudNet classification indicated mixed-phase conditions and potential aerosol–cloud interactions driven by mineral dust acting as ice-nucleating particles. In parallel, ATLID captured a regional-scale dust event on 4–5 March 2025, clearly resolving two distinct dust layers and an overlying cirrus layer. Lidar ratios and depolarization values from ATLID were consistent with ground-based PollyXT measurements. These results highlight the value of multi-instrument synergy in characterizing complex atmospheric processes and affirm CARO’s strategic role in satellite validation activities within the Eastern Mediterranean and Middle East and North Africa (EMMENA) region.
Keywords: Aerosol-cloud-dynamic interaction; Multi-instrument platforms; Satellite recordings; Eastern Mediterranean and Middle East and North Africa region (EMMENA)